Effect of Lactobacillus Acidophilus on IL-17 Expression Gene Levels in the Liver of Fetal Mice Infected with Entamoeba Histolytica - Saleh, Ahmed Hamad (American Journal of Biology and Natural Sciences, 2025)
Background & aim: Gram-positive lactic acid-producing bacteria belong to the broad and varied family Lactobacillaceae. Many mammals have gut microbiota, which includes these healthy bacteria that are commonly utilized as probiotics. Therefore, the study aimed to evaluate the effect of Lactobacillus Acidophilus on IL-17 expression gene levels in the liver of fetal mice infected with Entamoeba histolytica. Materials & methods: 40 distinct traditional yoghurts were obtained from Kirkuk marketplaces in the area at March 2025. while, 85 Random stool samples were taken from diarrheal patients at Azadi Teaching Hospital between March to Aril 2025. 20 adult albino mice were acquired from Tikrit University’s Veterinary College and mice were divided as follow (4 female and male in each group). Control group. Female mice injected E. histolytica. Female mice treated with Lactobacillus acidophilus. Female mice injected with E. histolytica and treated with Lactobacillus acidophilus concentrated filtrate for two weeks. The fetal liver was carefully cut up and spread out to small sections for histological and gene expression study. Results: The current study’s findings indicate that the overall prevalence of E. histolytica was 15/85 (17.6%). for histological examination, fetal livers of the infected group showed thickening of the central vein wall with degeneration and necrosis of hepatocytes, and decreased in hematopoietic elements, while, in L. acidophilus group, Sections prepared from the livers of fetuses in this group were similar to the normal group, as the central veins and hepatocytes were normal. in treated group, Cross-sections of the livers of fetuses in this group showed improvement compared to the infected group, as there was an improvement in hepatic cells, the amount of hematopoietic elements, and megakaryotic cells, but there continued to be thickening of the walls of some blood vessels and degeneration of some hepatic cells. The results showed that gene expression in studied groups, the mean of folding changes in infected group was 6.592, while in control, folding changes was 8.267. In L. acidophilus group, folding changes was 13.098. In treated group, folding changes ranged was 9.062. The results showed a significant (P=0.001) increase in gene expression in patients compared to the control group. Conclusions: it was found that infection with E. histolytica led to an increase in the expression levels of the IL-17 gene in the liver of fetal mice, while Lactobacillus Acidophilus played an effective role in regulating the expression of the IL-17 gene and liver protection.